DNA modification under mild conditions by Suzuki-Miyaura cross-coupling for the generation of functional probes. - Lercher, L; McGouran, J; Kessler, B; Schofield, C; Davis, B (2013)
Quick and clean: A method for Pd-catalyzed Suzuki-Miyaura cross-coupling to iododeoxyuridine (IdU) in DNA is described. Key to the reactivity is the choice of the ligand and the buffer. A covalent [Pd]-DNA intermediate was isolated and characterized. Photocrosslinking probes were generated to trap proteins that bind to epigenetic DNA modifications.